Some factors affecting the concentration of the aroma compound 2-acetyl-1-pyrroline in two fragrant rice cultivars grown in South China - Piebiep Goufo (2018)
The fragrance potential of two fragrant rice (Oryza sativa L.) cultivars grown in South China was investigated in this study using headspace SPME and static headspace in conjunction with GC-MS. About a five-fold difference of 2-acetyl-1-pyrroline (2-AP) levels were observed among the two fragrant rice cultivars, with Guixiangzhan having the highest content (3.86 μg·g-1) comparable to that obtained with Thai KDML 105 rice. Other compounds instead of 2-AP were assumed to contribute to the characteristic aroma of Peizaruanxiang. The two cultivars were subjected to two preharvest treatments (planting density and harvest date) and different storage conditions (3 to 6 months at -4, 8, 20, and 30°C). Results were discussed in terms of grain yield, milling quality, grain appearance, and amylose and protein contents of rice samples associated with differing treatments. Highest 2-AP concentrations were obtained for Guixiangzhan and Peizaruanxiang with lower planting densities, the earliest harvesting time of 10 days after heading, the shortest storage time of 3 months, and the lowest storage temperature of -4°C. These findings indicate that manipulating pre- and postharvest treatments can greatly improve the specific attributes of the domestically produced cultivars. With that in mind, China could effectively increase its share of the domestic market of fragrant rice and even tap into the international market. © Higher Education Press and Springer-Verlag Berlin Heidelberg 2010.